Mortality in Emergency Services in a University Teaching Hospital: A Retrospective Study - Shrestha, Tirtha Man; Aacharya, Ramesh P; Neupane, Ram P; Prajapati, Bigyan (Journal of Institute of Medicine Nepal, 2019)
Introduction: Emergency services are the gateway between the community and hospital that provides 24-hour access for most needy patients in critical and emergency conditions. Mortality rate varies in emergency department across the world and even in different emergency units of the same hospital. This retrospective study was done in adult emergency services of a tertiary hospital to determine mortality rate and analyze causes of death. Methods: A retrospective observational study of mortality cases to analyze mortality rate and causes of death of patients for a period of 6 months between October 2017 to March 2018 was carried out in the adult emergency services of Tribhuvan University Teaching Hospital, Kathmandu. Data required were collected from copies of death certificates. Results: During the study period, a total of 128 patients died in emergency, accounting 0.5% of total patient. Male deaths (52.3%) were slightly higher compared to female deaths (47.7%). Age group 66-75 years had the highest (24.2%) of total mortalities in the emergency. The most common immediate cause of death was sepsis/septic shock (21.9%) followed by cardiopulmonary arrest, aspiration, respiratory failure, other causes of shock and poisoning. The commonest antecedent cause of death was attributed to respiratory causes. Similarly, the most common contributory cause of death was chronic obstructive pulmonary disease. Conclusion: Older age group is prone to the mortality risk. Sepsis/septic shock was the most common immediate cause of death. Pneumonia was the most common antecedent causes of death. Chronic obstructive pulmonary disease was the commonest contributory cause.